'Long term impacts of a mega event: Case study Weymouth (London 2012)'. (15th November 2022) - Sadd, Debbie; Nguyen, Hai
Abstract: This paper investigates the long‐term impacts of a mega event, using the case of the London 2012 Olympics' impacts on Weymouth and Portland (as a joint destination in Southern England). The study used the 2 sets of data, collected in 2003 and 2017, containing the residents' perceptions before and after the event. The findings revealed important changes in terms of residents' perceptions towards the impacts of the London 2012 Olympics over the 14 years, such as an improvement in perceived positive impacts, a higher level of tourism involvement, the better perception of destination attributes, the relationship between destination nature attributes and the perceived negative impacts, and the more significant role of the perceived negative impacts. Different implications for the UK tourism industry, in particular British seaside resorts, and a wider context are also discussed. Abstracta: Este artículo investiga los impactos a largo plazo de un megaevento, utilizando el caso de los impactos de los Juegos Olímpicos de Londres 2012 en Weymouth y Portland (como destino conjunto en el sur de Inglaterra). El estudio utilizó los 2 conjuntos de datos, recopilados en 2003 y 2017, que contenían las percepciones de los residentes antes y después del evento. Los hallazgos revelaron cambios importantes en cuanto a las percepciones de los residentes sobre los impactos de los Juegos Olímpicos de Londres 2012 durante los 14 años, como una mejora en los impactos positivos percibidos, un mayor nivel de participación en el turismo, una mejor percepción de los atributos del destino, la relación entre atributos de la naturaleza del destino y los impactos negativos percibidos, y el papel más significativo de los impactos negativos percibidos. También se analizan diferentes implicaciones para la industria del turismo del Reino Unido, en particular los balnearios británicos, y un contexto más amplio.